KAJIAN POROSITAS TANAH LEMPUNG BERPASIR DAN LEMPUNG BERLIAT YANG DITANAMI JAGUNG DENGAN PEMBERIAN KOMPOS (STUDY OF SANDY LOAM AND CLAY LOAM SOIL POROSITIES ON PLANTED MAIZE WITH COMPOST APPLICATION) - Armiselin Ch. Salawangi; Jeanne Lengkong; Djoni Kaunang (COCOS, 2020)
ABSTRACTThe research aims to determine the effect of compost on soil porosity of sandy loam and claysoils and to see its effect on the growth of Maize plants. This research was conducted at Greenhouseand at Soil Physics and Soil Conservation Laboratory from May until June 2017. The results showedthat the addition of compost to soil can increase soil porosity and also the addition of compost to clayeytextured soil increased the porosity compared to the sandy loam textured soils. Application of composttends to increase plant height and dry weight on all age of plants; i.e. 10 days after planting, 30 daysafter planting and 40 days after planting. Application of compost at a dose of 10 tonnes/ha gives thehighest plant height on sandy loam soils and the heaviest plant dry weight on clayey loam soils.Keywords:Compost, Porosity